Q. 74.2( 61 Votes )

Let f, g : R &rar

Answer :

Given: f(x) = x + 1, g(x) = 2x – 3.

To find: f + g, f - g, 

     (f + g)x = f(x) + g(x)


     (f + g)x = x + 1 + 2x - 3 

   ⇒ (f + g)x = 3x - 2

And,

    (f - g)x = f(x) - g(x)


  (f - g)x  = (x + 1) - (2x - 3)


 ⇒ (f - g)x = x +1 - 2x + 3

  ⇒ (f - g)x = 4 - x

And,






Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Find the domain oNCERT - Maths

A function f is dNCERT - Maths

Which of the follNCERT - Maths